International dispute settlement in an evolving global society : constitutionalization, accessibility, privatization - Vicuña, Francisco Orrego (C.U.P. CambridgeGB, 2004)
Focuses on the development of international constitutional law in a global society; the increasing access of the individual; and the developing role of international private arbitration. Discusses recent thought and proposals concerning a new role for the International Court of Justice in performing judicial constitutional functions. Addresses the question of the eventual establishment of an International Constitutional Court.